Karakteristik dari penderita cedera medula spinalis traumatik di RSUP Haji Adam Malik Medan - Benny dr; Otman Siregar (Majalah Kedokteran Nusantara The Journal Of Medical School, 2012)
Background : Traumatic spinal cord injury was associated with high mortality rate, disabilities, prolonged rehabilitation and treatment, and high economic burden.Aim : Preventive measures can only be carried out through identification of the variables associated with this condition through an extensive and comprehensive epidemiology study.Methods : Collection of secondary data that was recorded in the patient’s medical record that diagnosed with traumatic spinal cord injury that was treated in Haji Adam Malik General Hospital Medan from January 2009 to December 2010. Results : At the period of two years (January 2009 to December 2010) as many as 44 medical records with diagnosis of traumatic spinal cord injury in Haji Adam Malik General Hospital were collected. Most of them were male (86.36%) in the productive age 21-40 years old (45.4%) with the most common causes was road traffic accident (45.5%) followed by fall from height (31.8%) and diving (2.3%). In general, patients arrived in the emergency room of Haji Adam Malik General Hospital after 8 hours (93%). The severity of spinal cord injury according to the Frankel Grading was dominated by Frankel A (40.9%) with the most level of neurological injury was twelfth thoracic (18%). Generally, patients sustaining traumatic spinal cord injury did not undergo surgery (86%). More than half of the patients (59%) were hospitalized less than 10 days with forced discharge as many as 19 patients (43.1%).Conclusion : Most of the patients with traumatic spinal cord injury in Haji Adam Malik General Hospital were male in their productive age with the most common cause was road traffic accident. Almost all of the patients arrived in Haji Adam Malik Medan after golden period hours. Preventive measures with the focus on reducing road traffic accident rate was the first priority followed by comprehensive counseling and education regarding the prevention, management and consequence of the traumatic spinal cord injury to the community.Keyword : injury; medula spinalis; traumatic; characteristic